2020
DOI: 10.3906/elk-2002-85
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between measured and estimated wind energy yield

Abstract: This paper proposes a power-speed (P-V) model of the wind turbine by assuming three different functions for the first performance region; cubic, quadratic and uncorrected cubic. These three functions have been compared with the manufacturer models of five different wind turbines which were installed in five different locations in Jordan; Tafila, Hofa, Fujeij, Al Rajef, and Deahan. The wind turbine of these wind farms are considered as large scale HAWT in the range of Mw. The generated P-V models are developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Wind farms that were operational in 2017 produced 132 MW of energy. Wind farms with a capacity of 155 MW are now being built and will be connected to the grid soon [43]. The rest of the paper is organized as follows: Section 2 describes the evolution of wind energy in Jordan; the energy extracted from wind turbines is presented in Section 3; cost analysis of the designed systems is presented in sections 4 and 5; the optimization problem is defined in Section 6; extrapolation method of wind speed is illustrated in Section 7; results and discussion are presented in Section 8; real measurements and the validation process are discussed in Section 9; and conclusions are presented in Section 10.…”
Section: Evolution Of Wind Energy In Jordanmentioning
confidence: 99%
See 1 more Smart Citation
“…Wind farms that were operational in 2017 produced 132 MW of energy. Wind farms with a capacity of 155 MW are now being built and will be connected to the grid soon [43]. The rest of the paper is organized as follows: Section 2 describes the evolution of wind energy in Jordan; the energy extracted from wind turbines is presented in Section 3; cost analysis of the designed systems is presented in sections 4 and 5; the optimization problem is defined in Section 6; extrapolation method of wind speed is illustrated in Section 7; results and discussion are presented in Section 8; real measurements and the validation process are discussed in Section 9; and conclusions are presented in Section 10.…”
Section: Evolution Of Wind Energy In Jordanmentioning
confidence: 99%
“…Such models are simple and easy to evaluate; however, they are free of detailed economic parameters and have a low accuracy level. Therefore, several research studies have used detailed economic models that are intrinsically about the time value of money [36][37][38][39][40][41][42][43][44][45][46][47][48]. Nevertheless, these models assume that the capital cost is constant for different energy production.…”
Section: Introductionmentioning
confidence: 99%
“…It can be observed from Figure 5 that λ needs to be maintained at an optimal value for all wind speeds-to run the WECS with maximum C p value [34][35][36][37][38][39][40]. This can be done only using variable speed operation with DFIG or PMSG where the rotor speed of the turbine can be adjusted at variable wind speed [9,[41][42][43][44][45]. Pitch angle control is usually used in large scale wind systems to fix the output power of the wind turbines at a specific limit, especially at high wind speed [28,46].…”
Section: Wind Turbine Characteristicsmentioning
confidence: 99%
“…In the literature, each category is characterized by several mathematical models. Table 1 shows a summary for the suggested mathematical models, used to represent q(v) [23][24][25][26][27][28][31][32][33][34]. As seen from this table, they are mainly divided into three main categories: polynomial power curves, exponential power curves and ratio power curves.…”
Section: Mathematical Representation Of the Dynamic Region Q(v)mentioning
confidence: 99%
“…By analysing the technical data of the commercial database, it can be concluded that the typical values for cut-in wind speeds are lower than 5 m/s (V I < 5 m/s), for rated wind speeds are between 10 and 17 m/s (10 < V R < 17 m/s) and 1 A summary for the suggested mathematical models, used to represent q(v) [11,[23][24][25][26][27][28] q(v)…”
Section: Commercial Wind Turbine Characteristicsmentioning
confidence: 99%